THE POSSIBILITIES OF TREATMENT OF PATIENTS WITH MALIGNANT NEOPLASMS OF THE FEMALE REPRODUCTIVE SYSTEM WITH METASTATIC BRAIN LESION - A. M. Zaytsev; E. G. Novikova; O. N. Kirsanova; M. I. Kurzhupov; E. A. Potapova (Исследования и практика в медицине)
Literature review over the last 10 years suggests that the brain is a rare target of metastasis of neoplasms of female reproductive system. However, over the past 20 years, incidence of secondary brain damage increased 6.5 times. Genital tumor metastasis in the brain is around 5%. The optimal treatment strategy of intracerebral metastases in this case is still an unsolved problem: the presence of foci of more than 3 cm surgery and then chemotherapy and radiation therapy is recommended; with smaller foci method of choice is a stereotactic brain radiosurgery followed by chemotherapy.Purpose. The Union of our own experience of treatment of patients with ovarian cancer (OC), cervical cancer (СС) and endometrial cancer (EC) with brain metastases and data from literature to develop the tactics of conducting patients with these diseases. Patients and methods. The neurosurgical department of P. Hertsen Moscow Oncology Research Institute, Branch, National Medical Radiology Research Center, Ministry of Health of Russia from 2007 to 2016 we treated 9 patients with metastatic OC in the brain, 6 patients with metastatic ER, 4 patients with metastatic cervical cancer.Resuts. Patients received microsurgical removal of metastatic tumors of the brain, followed by complex treatment, so they achieved a high median overall survival: patients with metastatic ovarian cancer - 14.0 months with diseasefree survival of 9.4 months. The survival median of patients with metastatic ER and cervical cancer was significantly lower, amounting to only 5.4 months.Conclusion. The article presents modern views on the problem of treating patients with intracranial metastases of malignant tumors of the female reproductive system. Our experience demonstrates that a comprehensive treatment, including neurosurgery, leads to increased survival of patients, providing a satisfac tory quality of life.